Towards chemical and nutritional inventory of Portuguese wild edible mushrooms in different habitats - Pereira, Eliana (2011)
Mushrooms have been valued as highly tasty/nutritional foods and as a source of compounds with medicinal properties. The huge mushrooms reservoir of Northeast Portugal must be chemically and nutritionally characterized for the benefit of populations and for the genetic conservation of wild macrofungi. Herein, a chemical, nutritional and bioactive inventory of potentially interesting species (and not yet characterized in literature) from different habitats (Castanea sativa, Pinus sp., Quercus sp., fields and mixed stands) was performed. Besides macronutrients with a well-balanced proportion, the studied wild mushrooms have also important micronutrients (vitamins) and non-nutrients (phenolics) with bioactive properties such as antioxidant potential. Furthermore, being a source of important antioxidants the wild species, mainly Suillus variegatus (Pinus sp. habitat), Boletus armeniacus (Castanea sativa habitat), Clavariadelphus pistillaris (Quercus sp. habitat), Agaricus lutosus (fields) and Bovista aestivalis (mixed stands), can be used in diet as nutraceuticals and/or functional foods maintaining and promoting health, longevity and life quality.